An Ethnopharmacological Survey on Medicinally Important Plants of Genus Salvia - Thorat, Bapu R.; Mali, Suraj N.; Yadav, Susmita; Gambhire, Vikas; Nagre, Dnyaneshwar T. (Combinatorial Chemistry & High Throughput Screening, 2025)
Lamiaceae (Labiatae) is a medicinally significant plant family featuring key species like Salvia aegyptiaca, S. cabulica, S. coccinea, S. glutinosa, S. officinalis, S. haematodes, S. hians, S. lanata, S. macrosiphon, S. moorcroftiana, S. spinosa, S. sclarea, and S. plebeia. These species exhibit diverse pharmacological activities attributed to essential oils and phytochemicals, including antioxidant, antiasthmatic, antitumor, anti-inflammatory, analgesic, etc. This review covers extensive phytomedicinal aspects of some important plants of the genus Salvia.
Keywords: phytochemistry